2007
DOI: 10.1200/jco.2007.11.6525
|View full text |Cite
|
Sign up to set email alerts
|

Early Interim 2-[18F]Fluoro-2-Deoxy-D-Glucose Positron Emission Tomography Is Prognostically Superior to International Prognostic Score in Advanced-Stage Hodgkin's Lymphoma: A Report From a Joint Italian-Danish Study

Abstract: PET-2 overshadows the prognostic value of IPS and emerges as the single most important tool for planning of risk-adapted treatment in advanced HL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
469
4
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 787 publications
(517 citation statements)
references
References 23 publications
22
469
4
11
Order By: Relevance
“…Many studies have confirmed that midtreatment FDG-PET images can predict clinical outcome in patients with HL or aggressive NHL, 22,23 and an association between a negative pretransplantation PET scan and a better outcome has was reported previously in the setting of high-dose therapy and autologous SCT with 2-year event-free survival rates ranging from 60% to 80%. 9,10 Patients with recurrent or progressive HL or aggressive NHL after autologous transplantation have no potentially curative treatment options other than alloSCT, and identifying the risk factors that influence the outcome of allografting would help to target optimal conditioning and immunologically based post-transplantatoin therapies for individual patients.…”
Section: Discussionmentioning
confidence: 63%
“…Many studies have confirmed that midtreatment FDG-PET images can predict clinical outcome in patients with HL or aggressive NHL, 22,23 and an association between a negative pretransplantation PET scan and a better outcome has was reported previously in the setting of high-dose therapy and autologous SCT with 2-year event-free survival rates ranging from 60% to 80%. 9,10 Patients with recurrent or progressive HL or aggressive NHL after autologous transplantation have no potentially curative treatment options other than alloSCT, and identifying the risk factors that influence the outcome of allografting would help to target optimal conditioning and immunologically based post-transplantatoin therapies for individual patients.…”
Section: Discussionmentioning
confidence: 63%
“…PET commonly influences RT fields in lymphoma by PET is also used to assess the response of lymphomas to CHT [120], either at the end of therapy, or as an interim measure, after e.g. 1-3 cycles [121][122][123][124]. Persistent interim tumor FDG uptake is a powerful negative prognostic factor in patients with…”
Section: Lymphomamentioning
confidence: 99%
“…However, the role of more sensitive techniques has become more important in the restaging process after initiation of treatment where it was shown to influence prognosis and treatment outcome [43], [44], [45] and [46]. Although it is widely accepted that a positive interim PET reflects poor prognosis, it is yet unknown whether a change of therapy in these patients will result in improved survival.…”
Section: Diagnosis and Stagingmentioning
confidence: 99%